Messages on pregnancy and family planning that providers give women living with HIV in the context of a Positive Health, Dignity, and Prevention intervention in Mozambique - Hilliard S; Gutin SA; Dawson Rose C (Dove Medical Press, 2014)
Starr Hilliard, Sarah A Gutin, Carol Dawson Rose Department of Community Health Systems, School of Nursing, University of California at San Francisco, San Francisco, CA, USA Background: Family planning is an important HIV prevention tool for women living with HIV (WLHIV). In Mozambique, the prevalence of HIV among women of reproductive age is 13.1% and the average fertility rate is high. However, family planning and reproductive health for WLHIV are under-addressed in Mozambique. This study explores provider descriptions of reproductive health messages in order to identify possible barriers and facilitators to successfully addressing family planning and pregnancy concerns of WLHIV. Methods: In 2006, a Positive Health, Dignity, and Prevention program was introduced in Mozambique focused on training health care providers to work with patients to reduce their transmission risks. Providers received training on multiple components, including family planning and prevention of mother-to-child transmission (PMTCT). In-depth interviews were conducted with 31 providers who participated in the training in five rural clinics in three provinces. Data were analyzed using qualitative content analysis. Results: Analysis showed that providers' clinical messages on family planning, pregnancy, and PMTCT for WLHIV could be arranged along a continuum. Provider statements ranged from saying that WLHIV should not become pregnant and condoms are the only valid form of family planning for WLHIV, to suggesting that WLHIV can have safe pregnancies. Conclusion: These data indicate that many providers continue to believe that WLHIV should not have children and this represents a challenge for integrating family planning into the care of WLHIV. Also, not offering WLHIV a full selection of family planning methods severely limits their ability to protect themselves from unintended pregnancies and to fully exercise their reproductive rights. Responding to the reproductive health needs of WLHIV is a critical component in HIV prevention and could increase the success of PMTCT programs. Keywords: prevention of mother-to-child transmission, provider messages, stigma, family planning, women, human immunodeficiency virus